Pengaruh Kreatifitas Guru Dalam Pembelajaran Tematik Terpadu Terhadap Peningkatan Minat Belajar Siswa Pada Pendidikan Dasar - Bongguk Haloho; Ulung Napitu; Ease Arent (Departement of Mathematics Education, 2023)
The method used in this study is a qualitative research method carried out by means of literature studies or library research that examines relevant theories.Learning in elementary schools in this study uses integrated thematic learning. This study aims to determine the effect of teacher creativity in integrated thematic learning on increasing students' learning interest in elementary schools. The results of this study indicate that integrated thematic learning greatly influences student learning interest, because thematic learning aims to increase students' understanding of concepts meaningfully. In this thematic learning students are required to be more active and think critically as well as in the student centered learning process. For this reason, teachers must be creative in implementing integrated thematic learning in order to achieve increased student interest in learning